Evaluating the predictive efficacy of the El-Ganzouri risk index for difficult laryngoscopy and intubation with King Vision™ video laryngoscope: A prospective cohort study - Aneeta Elizabeth Baby; Moses Charles D’souza; Mathangi Krishnakumar; Dicin Davis Kavalakkatt (Indian Journal of Anaesthesia)
Background and Aims: El-Ganzouri risk index (EGRI) scoring is a predictive tool for difficult video laryngoscope (VL) guided tracheal intubation, and its use has been studied for various VLs. This study evaluates the predictive value of EGRI scoring for difficult laryngoscopy and tracheal intubation with King Vision™ VL. Methods: Airway assessment was performed preinduction using the EGRI score. Following induction, initial laryngeal visualisation with a Macintosh blade identified the Cormack–Lehane grade. Final laryngoscopy and tracheal intubation were done using the King Vision™ VL, assessing the view with Percentage of Glottic Opening (POGO), Fremantle scores and ease with the modified Intubation Difficulty Scale. EGRI’s predictive power was evaluated through statistical analyses using Chi-square, t-test and receiver operating characteristic (ROC) curve. Statistical Package for the Social Sciences version 21.0 was used for analysis. Results: A total of 250 patients were included in the study, and the cut-off value of EGRI was 4. EGRI was assessed using the POGO and Fremantle scores for the view obtained during VL. The optimal cut-off for EGRI score was 3. ROC for difficult airways was calculated and compared to other scores. Sensitivity, specificity and area under the curve (AUC) were 82%, 86% and 0.9, respectively, for the POGO score and 74%, 92% and 0.85, respectively, for the Fremantle score. The ease of tube placement when assessed using a modified intubation difficulty scale was evaluated, and the sensitivity, specificity and AUC values were 95%, 86% and 0.94, respectively. Conclusion: EGRI scoring can effectively predict difficult laryngoscopy and intubation with the King Vision™ video laryngoscope.